Content-Based Citation Analysis of Open Access and Non-Open Access Medical Articles Using Opinion Mining of Citances - Khadijeh Jokar; Maryam Yaghtin; Hajar Sotudeh; Mahdieh Mirzabeigi (مدیریت اطلاعات سلامت, 2020)
Introduction: Scientific communities have always been concerned about validity of open-access articles. Given the challenges of quantitative citation analysis in evaluating scientific articles, content-based citation analysis, including opinion mining of citances, can bring about more transparent results about their validity. In view of this, the present study compared the opinions contained in citances about open-access and non-open-access articles.